Aktifitas Pembelajaran Bagi Anak Usia Dini dalam Meningkatkan Kematangan Karakter Religius - Darajat, Muhaiminah (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2025)
ABSTRACT. This article aims to describe the character values ??of brotherhood with the principle of psychology through religious activities and culture at Al-Ikhlas Elementary School, Lumajang Regency, East Java—data collection techniques employed observation, interviews, and documentation studies. The main data sources were the principal, vice principal, and homeroom teacher. The stages of data analysis followed the pattern of the reduction stage, data presentation stage, making temporary conclusions, and verification activities. The research findings concluded that character education at Al-Ikhlas Elementary School was developed using the whole school development approach, namely the alignment of the vision and mission of quality character education effectively and efficiently. In addition, the application of character education is formed in the interaction of teachers and students with respect, empathy, and affection. Good social interaction between students is also controlled by teachers to create an attitude of mutual respect and a comfortable atmosphere in learning and will encourage students to excel in the school environment. Keywords: learning activities, early childhood, character, religious